The relationship between public stigma, self-stigma, and non-suicidal self-injury in outpatient adolescents: a cross-sectional study - Guo, Qing; Wang, Jiayuan; Wang, Ruofei; Wang, Ruofan; Liu, Zikang (Frontiers in Psychiatry, 2025)
IntroductionStigma has a profound impact on the mental health of adolescents. However, empirical evidence on the association between stigma and non-suicidal self-injury among outpatient adolescents remains limited. This study aims to investigate the levels of stigma and self-injury among outpatient adolescents and to explore the relationship between stigma and self-injury.MethodsA total of 130 adolescents aged 12 to 18 who met the DSM-5 diagnostic criteria for non-suicidal self-injury and visited the psychiatric outpatient clinic between February and October 2024 were recruited for the study. The assessment included the adolescent self-harm questionnaire, the self-stigma of psychiatric disorders scale, the perceived devaluation-discrimination scale, and the Eysenck personality questionnaire-junior version. Statistical analyses were conducted using SPSS 26.0 and Rx64 4.0.3, with regression analyses employed to examine the effects of stigma and personality traits on the severity and frequency of self-injury among outpatient adolescents.Results(1) Among the 130 outpatient adolescents, the mean score for self-stigma was 75.13 ± 14.28, and the mean score for public stigma was 32.35 ± 6.25. A total of 63 adolescents (48.50%) exhibited a high severity of self-injurious behavior. (2) The proportion of adolescents with high severity of self-injury was significantly higher among those with divorced parents (χ²=5.898, P = 0.015) and those with a family history of psychiatric disorders (χ²=9.922, P = 0.003). Moreover, adolescents with a family history of psychiatric disorders had a higher frequency of self-injury compared to those without such a history (t=-2.637, P = 0.009). (3) The frequency of self-injury among outpatient adolescents was positively correlated with self-stigma (r=0.343, P<0.001). Additionally, the severity of self-injury was positively correlated with self-stigma (r=0.289, P<0.001), neuroticism (r=0.226, P<0.01), extraversion-introversion (r=0.232, P< 0.01), and psychoticism (r=0.233, P<0.01). (4) Family history of psychiatric disorders and self-stigma can partially predict the frequency of self-injury among outpatient adolescents (F = 3.344, p<0.01); self-stigma is a risk factor for the severity of self-injury in this population (OR = 1.05, 95% CI: 1.01-1.10).ConclusionsOutpatient adolescents with a family history of psychiatric disorders and higher levels of self-stigma exhibit greater frequencies of self-injury; furthermore, those with elevated self-stigma show higher severity of self-injury.